2012
DOI: 10.3855/jidc.2215
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of bacteremia due to an unusual pathogen, Comamonas testosteroni in Iran and a review literature

Abstract: Here we describe two cases of bacteremia caused by Comamonas testosteroni in two malignant patients, a 10-year-old boy with brain medulloblastoma and a 19-year-old girl with osteosarcoma admitted in the same hospital at short intervals. This is the first report in Iran on this low inherent virulence organism as a human pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 28 publications
(15 reference statements)
1
28
0
4
Order By: Relevance
“…In past reports, the predisposing factors have been malignant disease, perforated appen dicitis, and intravenous drug abuse, among others (7). Before this event, our patient had not experienced any peritonitis.…”
Section: Discussionmentioning
confidence: 47%
“…In past reports, the predisposing factors have been malignant disease, perforated appen dicitis, and intravenous drug abuse, among others (7). Before this event, our patient had not experienced any peritonitis.…”
Section: Discussionmentioning
confidence: 47%
“…C. testosteroni is usually sensitive to a broad range of antibiotics, including aminoglycosides, cephalosporins, fluoroquinolones, carbapenems, piperacillintazobactam, cephalosporins, and trimethoprimsulfamethoxazole [15] . According to the survey by Farshad et al [1] , 32 out of 35 reported cases of human infection by this bacterium were Parolin M et al . C. testosteroni peritonitis in children promptly responsive to antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…testosteroni is a gramnegative aerobic bacillus that is found in various environments, including soil, water, plants, and animals. In spite of its wide environmental distribution, there are few reports on its involvement in human infections [1] . Most of the reported infections by this organism are communityacquired, however some authors suggested that it can also survive for a long time in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations